Rheological and slip casting behaviour of low clay containing translucent whitewares - Çapoglu, A; Kutbay, I (Trans Tech Publications Ltd, 2002)
The rheological and casting behaviour of slips, made with the starting materials for a novel whiteware, have been studied. The starting materials consisted of coarse and fine prefired (chamotte) material and ball and china clays. The prefired material was composed of anorthite as the major phase with mullite and glass as minor phases. The whiteware comprised 50 (w)% coarse prefired (similar to7.3 mum), 38 (w)% fine prefired (similar to1.5 mum), 6 (w)% china clay and 6 (w)% ball clay. The whiteware was unusual in that it contained only 12 (w)% clay compared to the usual range from 30-60 (w)%. The clay content had been reduced in order to minimise the anisotropy of shrinkage during drying and firing, which arise from clay particle alignment. The effect of different deflocculants and a binder (PVA) on the rheological properties of slips made with the individual starting materials were studied. All the deflocculants studied except gum Arabic reduced the yield stress and absolute viscosity of each slip. However, the PVA addition increased the absolute viscosity of slip in which it didn't contain any deflocculant. The full body slip containing PVA could be deflocculated with a mixture of sodium silicate and sodium carbonate. Casting trials showed that it was possible to produce successful casts with all the deflocculated slips, Unless slip is well deflocculated when PVA was present casts were found to crack while on drying in the mould. The casts containing PVA were highly porous even tough they were formed from deflocculated slips, It appears that PVA prevents the particles from packing closely together. This problem was overcomed by reducing the water content of deflocculated slip.
7th Conference of the European-Ceramic-Society -- SEP 09-13, 2001 -- BRUGGE, BELGIUM
Keywords: low-clay; translucent; whiteware; rheology; slip casting; chamotte; anorthite; mullite